Implementation of Values of Tolerance Between Religions at SMA Negeri 1 Padang - Firly Nazilah Putri; Rido Putra (Badan Penerbit STIEPARI Press, 2025)
This study aims to determine the implementation of interfaith tolerance values in SMA Negeri 1 Padang, identify forms of interfaith tolerance values education programs, and analyze supporting and inhibiting factors in the implementation of these values. The method used is a qualitative method with field research and a qualitative descriptive approach. The data sources in this study consist of primary and secondary sources, namely the principal of SMA Negeri 1 Padang, the Deputy Head of Curriculum, the Deputy Head of Public Relations, Islamic Religious Education and Citizenship Education teachers, and nine students from various religious backgrounds. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The validity of the data is tested using triangulation techniques of sources, time, and techniques. Overall, the results of the analysis show: First, SMA Negeri 1 Padang has succeeded in creating an inclusive environment and social interaction between students from various religious backgrounds takes place in an inclusive and harmonious manner. Second, the school organizes programs such as interfaith discussions, increasing insight into diversity, diversity seminars, socialization of tolerance values, and social services. These programs are effective in increasing students' understanding and solidarity towards diversity. Third, supporting factors in the implementation of tolerance values include: school policies that support diversity, the active role of teachers and parents, and good social relations between students, and there are several inhibiting factors such as the introverted character of students and potentially offensive joking interactions. Overall, the school has shown significant efforts in forming a tolerant and harmonious environment amidst diversity. The researcher recommends that SMA Negeri 1 Padang can be an example in implementing tolerance values between religious communities in the school environment